1999
DOI: 10.1051/rnd:19990145
|View full text |Cite
|
Sign up to set email alerts
|

Development of intra- and intermuscular adipose tissue in growing Large White and Meishan pigs

Abstract: -Lipogenic enzyme activities of porcine intra-and intermuscular adipose tissues were determined in growing lean (Large White) and fat (Meishan) pigs. The activities of acetyl-CoA-carboxylase (ACX), malic enzyme (ME) and glucose-6-phosphate dehydrogenase (G6PDH) were compared in both breeds and at both adipose sites. All

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
21
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 17 publications
6
21
0
2
Order By: Relevance
“…This is consistent with previous findings indicating that the ubiquitously expressed ME1 is positively associated with the deposition of porcine intramuscular adipose (r = 0.9, P < 0.01) (Mourot and Kouba, 1999). Expression patterns of MDH1, MDH2 and ME1 genes In summary, our results suggest that MDH1, MDH2 and ME1 are important for porcine adipose deposition and are therefore promising candidate genes for the pig fat mass trait.…”
Section: Resultssupporting
confidence: 92%
“…This is consistent with previous findings indicating that the ubiquitously expressed ME1 is positively associated with the deposition of porcine intramuscular adipose (r = 0.9, P < 0.01) (Mourot and Kouba, 1999). Expression patterns of MDH1, MDH2 and ME1 genes In summary, our results suggest that MDH1, MDH2 and ME1 are important for porcine adipose deposition and are therefore promising candidate genes for the pig fat mass trait.…”
Section: Resultssupporting
confidence: 92%
“…Moreover, Lazo et al [24] reported that intramuscular fat content in LD muscle dramatically increased during the growth period, suggesting that for this criterion, the CR pig was superior to the other local breeds. The higher intramuscular fat content in CR pigs was consistent with a fatter carcass and could also be explained by a higher lipogenic capacity in intra muscular adipose tissues as suggested for backfat adipose tissue [29].…”
Section: Effect Of Breed On Growth Performance and Carcass Traitsupporting
confidence: 67%
“…The research of Dvořáková et al (2012) indicated allele C was significantly associated with back fat depth and allele G in exon 3 of the FTO with muscling traits in commercial pigs. Moreover, different genotypes, such as H-FABP , leptin receptor (Tyra et al, 2011), and sterol regulatory element binding transcription factor 1 gene (Chen et al, 2008) It is well known that the order of adipose deposition is initially subcutaneous, followed by intermuscular and finally at intramuscular adipose sites (Mourot and Kouba, 1999). In other words, more IMF is deposited in the later stages of animal development.…”
Section: Discussionmentioning
confidence: 99%